2008
DOI: 10.1042/bst0360575
|View full text |Cite
|
Sign up to set email alerts
|

The methyl-CpG-binding protein MeCP2 and neurological disease

Abstract: The methyl-CpG-binding protein MeCP2 was discovered over 15 years ago as part of a search for proteins that selectively bind methylated DNA. It is a nuclear protein that is largely chromatin-bound and has a strong preference for binding to methylated DNA sequences in vivo. Evidence from model systems shows that MeCP2 can recruit the Sin3a co-repressor complex to promoters leading to transcriptional repression, therefore suggesting that MeCP2 can interpret the DNA methylation signal to bring about gene silencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 92 publications
0
51
0
Order By: Relevance
“…Nevertheless by focusing on a single gene it is possible to gain insights into the possible mechanisms whereby HMGN1 affects the global phenotype. We focused on MeCP2 as a gene regulated by HMGN1 because it is highly expressed in brain (23) and because it is well documented that misexpression of MeCP2 or mutations in MeCP2 are strongly linked to behavioral abnormalities in human and mice (55)(56)(57)(58). Our findings that HMGN1 is associated with regulatory regions of MeCP2 in both human and mouse brain tissues and that the MeCP2 levels in brain tissues from mice that either overexpress or lack HMGN1 are either reduced or elevated, respectively, suggest that HMGN1 modulates MeCP2 levels in vivo.…”
Section: Hmgn1mentioning
confidence: 99%
“…Nevertheless by focusing on a single gene it is possible to gain insights into the possible mechanisms whereby HMGN1 affects the global phenotype. We focused on MeCP2 as a gene regulated by HMGN1 because it is highly expressed in brain (23) and because it is well documented that misexpression of MeCP2 or mutations in MeCP2 are strongly linked to behavioral abnormalities in human and mice (55)(56)(57)(58). Our findings that HMGN1 is associated with regulatory regions of MeCP2 in both human and mouse brain tissues and that the MeCP2 levels in brain tissues from mice that either overexpress or lack HMGN1 are either reduced or elevated, respectively, suggest that HMGN1 modulates MeCP2 levels in vivo.…”
Section: Hmgn1mentioning
confidence: 99%
“…The role of this transcription factor is incompletely understood. Until recently, on the basis of animal studies primarily in embryonic or early neonatal brain, Mecp2 was considered a translational repressor (2,3). Recently, however, Skene et al (4) found in neuronal nuclei of mature (6-8 wk) WT littermates of Mecp2 null males that Mecp2 expression is ≈fivefold greater than that at birth.…”
mentioning
confidence: 99%
“…It also involves chromatin components and chromatin-binding/-modifying proteins, which are implicated in the establishment and maintenance of a condensed chromatin state, also referred to as facultative heterochromatin (1). Deregulation of these chromatin regulatory factors and aberrant chromatin modifications play important roles in various human diseases, including cancers, developmental abnormalities, and neurologic disorders (2)(3)(4)(5)(6). Moreover, several recent reports have linked histone modifications and infectious diseases (7).…”
mentioning
confidence: 99%